2012
DOI: 10.1007/s10995-012-1163-z
|View full text |Cite
|
Sign up to set email alerts
|

Adjusted Effects of Domestic Violence, Tobacco use, and Indoor Air Pollution from Use of Solid Fuel on Child Mortality

Abstract: Studies that have separately examined the consequences of gender based violence upon women, use of solid fuel for cooking, and mother and father's use of tobacco on child health have concluded that they serve as risk factors for maternal and child health. Some authors have implied that these studies may have run the risk of overestimating the burden of disease of one factor over another. In this paper, we included all four factors in the same model to estimate their adjusted effects on child mortality, control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 42 publications
7
24
0
Order By: Relevance
“…In addition, this study also did not measure actual levels and patterns of exposure to emission from cooking smoke due to the lack of such objective measures in DHS data. Other important covariates, for example, “cooking under chimney” and “presence of windows in cooking area”, have been noted in previous studies [27, 28]; however, this information was not measured in the PDHS 2013 dataset.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this study also did not measure actual levels and patterns of exposure to emission from cooking smoke due to the lack of such objective measures in DHS data. Other important covariates, for example, “cooking under chimney” and “presence of windows in cooking area”, have been noted in previous studies [27, 28]; however, this information was not measured in the PDHS 2013 dataset.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the use of solid fuels in homes have been reported to be the leading single environmental cause of ill health [61–63]. Previous studies have indicated that children living in homes using solid fuels for cooking are at a greater risk of dying from acute respiratory illnesses [6466]. According to the WHO [25], about half of all deaths among under-five children in the year 2014 was caused by acute lower respiratory infections triggered by the use of solid fuels.…”
Section: Discussionmentioning
confidence: 99%
“…14,19 The violence is commonly experienced by women at various phases of the life cycle from prenatal period, infancy, childhood, adolescence, reproductive age to old age in different forms. 4,12,[20][21][22] In addition, the raped women are rejected by their families and their communities, among them those who had a child from rape, widowhood, husband abandonment and gang rape have more risk of rejection. 23 Besides, rape results not only in physical and psychological trauma, but can destroy family and community structures.…”
Section: Gender Based Violencementioning
confidence: 99%